Equivalent slot thermal conductivity and back-iron extension effects on machine cooling - Zhang, Fengyu; Gerada, David; Xu, Zeyuan; Zhang, He; Gerada, Chris (2019)
Back-iron Extension (BIE) is an effective thermal management technique which reduces the winding temperatures by projecting part of the back iron into the center of slot, thereby shortening the heat transfer path between the coil and back iron. Based on an existing concentrated-wound traction motor, this paper investigates the effects of equivalent slot thermal conductivity of coil on the optimal back iron extension geometry and temperature reduction.